Improving Science Learning Outcomes Through Two Stay Two Stray Assisted by Concrete Media - Putra, Agung Kusuma; Jampel, I Nyoman; Japa, I Gusti Ngurah (Universitas Pendidikan Ganesha, 2020)
Science learning is one of the subjects in elementary schools to be able to develop students' process skills related to natural phenomena that occur as a source of knowledge. Science learning should be student-centered, but the learning process is still teacher-centered and only uses the lecture method. This study aims to analyze the effect of the Two Stay Two Stray learning model (TSTS) assisted by concrete media on the science learning outcomes at fifth grade primary school 2019/2020. Quasi-experiments became the type of this study with a non-equivalent post-test only control group design study design. The population in this study were 211 elementary school students. Sampling is done through random sampling by lottery techniques. The sample in the experimental group was 22 students and the sample in the control group was 26 students. The science learning outcomes test is a multiple-choice instrument used when collecting data through instrument validation conducted by experts in the field of science and has been tested. The data obtained were then analyzed using the t-test with the polled variance formula which showed that tcount> t table (t count = 6.16> t table = 1.68). This means that there are significant differences in science learning outcomes between groups of students who are taught with the Two Stay Two Stray (TSTS) learning model assisted by concrete media and groups of students who are taught conventionally. Based on these results it can be concluded that the Two Stay Two Stray learning model (TSTS) assisted by concrete media affects the learning outcomes of fifth-grade students.